2014
DOI: 10.4103/0973-1482.131413
|View full text |Cite
|
Sign up to set email alerts
|

The investigation of changes in proteins expression (Apolipoprotein A1 and albumin) in malignant astrocytoma brain tumor

Abstract: The vascular microenvironment of glioma play a major role in determining the pathophysiological character is tics of the tumor. apo A1 and albumin are very significant due to their functional consequences in glioma tumor growth, migration and angiogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…Our discovery dataset and literature also pointed at upregulation of several apolipoproteins in gliomas and meningiomas (12,31,32). APOE plays a vital role in redistribution of intracellular lipid and tissue reconstruction in CNS through a receptor dependent pathway.…”
Section: Discussionsupporting
confidence: 61%
“…Our discovery dataset and literature also pointed at upregulation of several apolipoproteins in gliomas and meningiomas (12,31,32). APOE plays a vital role in redistribution of intracellular lipid and tissue reconstruction in CNS through a receptor dependent pathway.…”
Section: Discussionsupporting
confidence: 61%
“…Therapies targeting neovascularization in malignant gliomas show promise in improving outcome[ 4 , 5 ]. Microvessel density (MVD) has been used to predict treatment outcome[ 6 , 7 ]. It has been reported that increased CD105-MVD correlates with shorter survival[ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…42 , 43 Moreover, Chimienti et al 44 reported that APOA inhibited the secretion of IL-6 by interfering with lipopolysaccharide signaling in a human astrocytoma cell line. Hashemi et al 45 discovered that APOA1 was a key oncogene in malignant astrocytoma tumors due to its functional consequences in tumor growth, angiogenesis and migration. As described previously, APOB is mainly responsible for the transportation of lipids, and methylation of APOB leads to the accumulation of extracellular lipids.…”
Section: Discussionmentioning
confidence: 99%